A primate perspective on oocytes and transgenerational PCOS. Issue 6 (June 2020) - Dumesic, Daniel A.; Wood, Jennifer R.; Abbott, David H.; Strauss, Jerome F.
Abstract: 'Androgenized' rodent models are widely used to explore the pathophysiology underlying human polycystic ovary syndrome (PCOS), including reproductive and metabolic dysfunction. Based on a recent study using a dihydrotestosterone (DHT)-treated murine model, it has been proposed that prenatal androgen excess alone can predispose to transgenerational transmission of PCOS. From RNA sequencing analysis of metaphase II (MII) oocytes of androgenized lineages, the authors speculated that oocyte factors, including up-regulation of cytotoxic granulosa-associated RNA binding protein-like 1 ( TiaL1 ), are sufficient to promote disease transfer across generations. Although this is an intriguing concept, it was not considered in the context of earlier publications in which the transcriptomes of human MII oocytes from PCOS women undergoing IVF were compared with women without PCOS. In one of these papers, a number of differentially expressed genes in PCOS MII oocytes ( TIAL1 was not differentially expressed) were found to have putative response elements in their promoters for androgen receptors and peroxisome proliferating receptor gamma, providing a mechanism for how excess androgens and/or metabolic defects associated with PCOS might affect female germ cells.